Landscape Features and Climatic Forces Shape the Genetic Structure and Evolutionary History of an Oak Species (Quercus chenii) in East China - Li, Yao; Zhang, Xingwang; Fang, Yanming (Frontiers in Plant Science, 2019)
Major topographic features facilitate intraspecific divergence through geographic isolation. This process may be enhanced by environmental isolation along climatic gradients, but also may be reduced by range shifts under rapid climatic changes. In this study, we examined how topography and climate have interacted over time and space to influence the genetic structure and evolutionary history of Quercus chenii, a deciduous oak species representative of the East China flora. Based on the nuclear microsatellite variation at 14 loci, we identified multiple genetic boundaries that were well associated with persistent landscape barriers of East China. Redundancy analysis indicated that both geography and climate explained similar amounts of intraspecific variation. Ecological differences along altitudinal gradients may have driven the divergence between highlands and lowlands. However, range expansions during the Last Interglacial as inferred from approximate Bayesian computation (ABC) may have increased the genetic diversity and eliminated the differentiation of lowland populations via admixture. Chloroplast (cp) DNA analysis of three intergenic spacers (2,866 bp in length) identified a total of 18 haplotypes, 15 of which were private to a single population, probably a result of long-term isolation among multiple montane habitats. A time-calibrated phylogeny suggested that palaeoclimatic changes of the Miocene underlay the lineage divergence of three major clades. In combination with ecological niche modeling (ENM), we concluded that mountainous areas with higher climatic stability are more likely to be glacial refugia that preserved higher phylogenetic diversity, while plains and basins may have acted as dispersal corridors for the post-glacial south-to-north migration. Our findings provide compelling evidence that both topography and climate have shaped the pattern of genetic variation of Q. chenii. Mountains as barriers facilitated differentiation through both geographic and environmental isolation, whereas lowlands as corridors increased the population connectivity especially when the species experienced range expansions.